2016
DOI: 10.21037/atm.2016.03.19
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging study in Duchenne muscular dystrophy

Abstract: Background: Duchenne muscular dystrophy (DMD) is a progressive muscle disorder associated with an intellectual deficit which is non-progressive. The aim of this study was to investigate brain microstructural changes in DMD and to explore the relationship between such changes and cognitive impairment.Methods: All participants (12 DMD patients, 14 age-matched healthy boys), intelligence quotients (IQs) [both full (FIQ) and verbal (VIQ)] were evaluated using the Wechsler intelligence scale for children China revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Boys may present specific learning disabilities such as dyslexia and impaired executive functions, namely problem solving, inhibition and working memory. 33 In addition, Astrea et al 37 demonstrated that 15 patients with DMD (age range = 19-44 years) demonstrated impairment in the ability to sequentially process auditory and visual information and attention. 6 A controlled study of diffusion tensor imaging (DTI) involving 15 boys with DMD showed significantly lower fractional anisotropy (FA) values in the spleni um of CC and these values were positively correlated with verbal IQ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boys may present specific learning disabilities such as dyslexia and impaired executive functions, namely problem solving, inhibition and working memory. 33 In addition, Astrea et al 37 demonstrated that 15 patients with DMD (age range = 19-44 years) demonstrated impairment in the ability to sequentially process auditory and visual information and attention. 6 A controlled study of diffusion tensor imaging (DTI) involving 15 boys with DMD showed significantly lower fractional anisotropy (FA) values in the spleni um of CC and these values were positively correlated with verbal IQ.…”
Section: Discussionmentioning
confidence: 99%
“…6 A controlled study of diffusion tensor imaging (DTI) involving 15 boys with DMD showed significantly lower fractional anisotropy (FA) values in the spleni um of CC and these values were positively correlated with verbal IQ. 37 …”
Section: Discussionmentioning
confidence: 99%
“…139 Using DTI-ROI-based approaches and selecting 16 different structures bilaterally, Fu and colleagues found changes in the corpus callosum and, in particular, in the splenium. 113 However, both the small size of ROI used and the lack of multiple correction comparisons are the limits of the study. Lv and colleagues, assessing motor-related brain cortex, found the smaller volume in the left primary sensorimotor cortex in DMD.…”
Section: Myotonic Dystrophy Type 1: Steinert’s Diseasementioning
confidence: 99%
“…First, qualitative results of fractional anisotropy images showed a deficit of neurons in various neuroanatomic areas of the two hemispheres (Figure ). Second, quantitative measurements, where various ROIs have been placed bilaterally in various neuroanatomic areas such as parietal, frontal, occipital, temporal lobes, genu, splenium of the corpus callosum, caudate nuclei, anterior and posterior cingulate, lenticular nuclei, anterior and posterior limb of the internal capsule, hippocampus, superior and middle cerebellar peduncle and thalamus, showed similar lesions; in DTI coloured maps, their corresponding fractional anisotropy showed numerically a neuronal deficit (Figures and ) …”
Section: Mri For Heart Muscles and Brainmentioning
confidence: 96%
“…Second, quantitative measurements, where various ROIs have been placed bilaterally in various neuroanatomic areas such as parietal, frontal, occipital, temporal lobes, genu, splenium of the corpus callosum, caudate nuclei, anterior and posterior cingulate, lenticular nuclei, anterior and posterior limb of the internal capsule, hippocampus, superior and middle cerebellar peduncle and thalamus, showed similar lesions; in DTI coloured maps, their corresponding fractional anisotropy showed numerically a neuronal deficit (Figures 4 and 5). 69,70 3 | CONCLUSIONS Duchenne muscular dystrophy is a complex disease that involves not only the striated muscles, but also the heart and the brain. A holistic approach by magnetic resonance imaging/spectroscopy may lead to an individual "heart and brain imaging map", facilitate risk stratification, serial follow-up and treatment evaluation, and serve as a reliable tool for future clinical trials in DMD patients.…”
Section: Brain Magnetic Resonance Imaging/ Spectroscopy (Bmri/bmrs)mentioning
confidence: 99%